Langkah Praktis Memulai Bisnis Online dalam Mengembangkan Potensi Generasi Muda Pembekalan Bagi Siswa Kelas 10-12 Yayasan Al-Kafhi Bekasi Utara - Ali Satri Efendi; Retno Setya Budiasningrum; Enny Diah Astuti; Dyan Yuliana; Rahmi Rosita; Jajang Setiawan (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Digital technology opens up great opportunities in the business world, especially online businesses. These opportunities are wide open to many people of various ages and backgrounds, especially young people, considering that their generation has the spirit to try various things, including starting a business. This community service activity aims to provide practical training to vocational high school students on how to start an online business. For two days, they were given an understanding of entrepreneurship, determining potential products, creating accounts on e-commerce, marketing strategies, simulations, and evaluations. This activity is expected to develop economic potential and independence from an early age, and be able to instill an entrepreneurial mindset that is adaptive to the development of the times.